Penerapan Aplikasi Sahabat Ibu Hamil (ASIH) terhadap Peningkatan Kualitas Pelayanan Antenatal di Pedesaan - Farhati Farhati; Nanan Sekarwana; Farid Husin (Politeknik Kesehatan Tanjung Karang, 2018)
Quality of antenatal care is important to reduce the maternal mortality rate. It associated with providing antenatal care according to standards and meet the expectations or satisfaction of pregnant women. However, today’s midwifery practise still show low compliance with standards, especially related to health education and pregnant women empowerment through the use of Maternal and Child Health media books. This research aimed to analyze the effect of “Aplikasi Sahabat Ibu Hamil” implementation to antenatal care quality improvement in rural areas. This study using quasi-experimental pre-post test design with control groups conducted in West Bandung regency with sample of 61 midwive and pregnant women, using checklists and questionnaires. Univariable analysis was done through Rash modeling, bivariable analysis using numeric categorical comparative test. The results indicated that the quality of antenatal services between control and treatment groups showed significant difference with p<0,01. Aplikasi Sahabat Ibu Hamil (ASIH) implementation served to increase midwive adherence to antenatal care standards by 47.2% and satisfaction of pregnant women by 43.8%. The proportion of good quality antenatal care were 84% in treatment groups and 37% in control group. Antenatal care without using ASIH will increase midwives’ risk of noncompliance in antenatal care standards 3.93 times, pregnant women dissatisfaction 4.4 times and poor quality of antenatal care 3.93 times compared with antenatal care using ASIH.